Мова права як унікальний напрям людської комунікації (теоретико-правові та філософські роздуми) - Лазарєв, В. В.; Lazariev, V. V.; Лазарєв Віктор Вікторович (Вісник Харківського національного університету внутрішніх справ. – 2022. – № 3 (98). – С. 26-34, 2022)
Досліджено особливості мови права як особливого напряму людської комунікації. Зауважено, що в сучасному світі зв’язок між правом і мовою виявляється на достатньо глибокому рівні та є достатньо складним і фундаментальним вираженням їх взаємодії. Зазначено, що мова права здебільшого пересічними громадянами та суспільством у цілому сприймається дещо специфічно, оскільки виглядає спеціалізованою, піднесеною і технічною, особливо її письмова форма. Наголошено на сучасних підходах і закликах щодо спрощення мови права та наближення її розуміння для кожної особи. Також порушено питання стосовно гендерної рівності під час використання мови права в сучасному світі.

The article is devoted to the study of the peculiarities of the language of law as a special direction of human communication. It has been noted that in the modern world, the connection between law and language appears at a sufficiently deep level and is a sufficiently complex and fundamental expression of their interaction. The research draws attention to the similarities and differences inherent in linguistics and jurisprudence. Attention has been focused on the fact that legal language is usually perceived somewhat specifically by ordinary citizens and society as a whole, as it looks specialized, elevated and technical, especially its written form. This is, in particular, due to the fact that constructions containing legal terminology, specialized legal terms, legal vocabulary are used to write a legal text, which leads to the fact that the language of law becomes incomprehensible to non-lawyers. Attention has been drawn to the peculiarities of the use of legal linguistics in the AngloSaxon law systems and in German-speaking countries. The approaches of researchers advocating for the simplification of the language of law have been considered, since, in their opinion, the language of law as a certain means of communication is characterized by “grandiloquence and verbosity”, which makes it difficult for the average citizen to understand it and does not allow them to fully familiarize themselves with normative documents and court decisions. The study also has raised the issue of gender equality when using the language of law in the modern world. Attention has been drawn to the fact that in foreign political and legal opinion, the statement is gaining more and more strength that if the goal of the law is really unlimited access of citizens to their constitutional rights to information and non-degradation of any gender, then the simplification of legal communication and gender-neutral writing should be its main goal.

Исследованы особенности языка права как особого направления человеческой коммуникации. Замечено, что в современном мире связь между правом и языком оказывается на достаточно глубоком уровне и достаточно сложным и фундаментальным выражением их взаимодействия. Отмечено, что язык права в основном рядовыми гражданами и обществом в целом воспринимается несколько специфически, поскольку выглядит специализированным, возвышенным и техническим, особенно его письменная форма. Отмечено современные подходы и призывы об упрощении языка права и приближении его понимания для каждого лица. Также поднят вопрос относительно гендерного равенства при использовании языка права в современном мире.
The language of law as a unique direction of human communication (theoretical legal and philosophical reflections)
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; право; law; мова; language; язык; мова права; language of law; язык права; формальна визначеність; formal certainty; формальная определенность; інтерпретація; interpretation; интерпретация; юридична лінгвістика; legal linguistics; юридическая лингвистика; лексика; vocabulary